Catholics in America: a history - Carey, Patrick W. (A Sheed & Ward book, 2008)
Rez.: "Beginning with a narrative history of Catholics and Catholicism in America, Patrick Carey brings the discussion through to current times, addressing the recent problems in the Church, women's roles, and responses to terrorism and war. He then goes on to include brief biographical sketches of important figures in the Church, and offers a chronology of important events. The result is one of the most comprehensive histories of Catholics in America available."--BOOK JACKET.